ECD-IMC: an integrated marketing communications model for selected Philippine higher education institutions - DAGUMBOY, ELOIDA (Jurnal Studi Komunikasi, 2022)
Private higher education institutions (HEIs) in the Philippines have been in turmoil due to three major occurrences: the Enhanced Basic Education Act of 2013, the Universal Access to Quality Tertiary Education Act of 2017, and the Coronavirus Disease. These contributed to the abating tertiary enrolment. One scheme for enduring the ordeal is the application of budgetary cuts. Competing in a scarcer market with financial constraints is an arduous task for marketing. The paper aimed to identify the most effective platform blend among numerous communication platforms employed in the industry by recognising the importance of integrated marketing communications (IMC) and maximising HEIs' return on marketing investments. About 380 students, parents, and administrators from five private HEIs in the National Capital Region offering Senior High School programs participated as survey respondents or interviewees. The paper utilised mixed methods, various statistical tools, and variance analyses. Among the twenty marketing communication platforms, the most efficient (efficiency rating>3.736) are referrals/word-of-mouth marketing, free entrance examination, website, scholarships/discounts, and social media. In contrast, in the lower quartile (efficiency rating<3.262) are billboards, television/radio/print ads, souvenir items, sending direct messages to prospective students, and newspaper articles. To some extent, the HEIs implementation level of the various platforms is aligned with communication platforms' efficiency ratings. Further, the study ascertained differences in the preference and reached ratings according to respondents' profiles. Finally, an Efficient, Coherent, and Dynamic (ECD)-IMC model was crafted to help HEI administrators/marketers improve their enrolment with the least possible costs and to provide reference to future researchers.